(3GdgjGcd GdJehjdjI (B/s - (3GHh GdaJhM, Ydi aVGdIs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 1994)
(3aj gPG GdcJGH JLO (B: (3JhVjM GdYdGbGJ GdYVhjI Hjf GdNUUI hUMI GdgjGcd GdJehdjI JJjM aMU hJTNjU hYdGL hJbhje GOGQI GdgjGcd GdJehdjI GSJNOGe GdbhGFe GdfbOjI aj GdJMOjO hGdJNWjW hGdJfXje YQV GdeDTQGJ GdeGdjI hGdGbJUGOjI hGdGMUGFjI hGdafjI dJbhje GdGOGA JHjGf CKGQ hGdbQGQGJ Ydi GNJdGd Ch UMI GdgjGcd GdJehjdjI (B.s
Keywords: (3gjGcd JehjfjIs